Comments on “Marine tether dynamics: retrieval and deployment from a heaving platform” By R.E. Baddour and W. Raman-Nair - Laura, Patricio Adolfo Antonio (2003)
The authors are to be congratulated for their excellent proposal and solution of the resulting mathematical model of the tether management system of a winch module in a marine environment (Baddour and Raman - Nair (2002). The effects of the heaving platform on the motions of the drum, tether and attached mass are analized in conjunction with the longitudinal one – dimensional vibrations of the tether taking into account the tether extensibility when dealing with the operation threshold of the system.